Aortoduodenal syndrome in a patient receiving maintenance haemodialysis. (11th November 2014) - Saigusa, Susumu; Ohi, Masaki; Imaoka, Hiroki; Inoue, Yasuhiro
Abstract : An 83-year-old man receiving maintenance haemodialysis presented with abdominal pain, fever and emesis. He was initially diagnosed with acute cholecystitis. His pain and fever improved with fasting and antibiotics, but he continued to suffer from anorexia and emesis. Enhanced abdominal CT scan showed evidence of superior mesenteric artery (SMA) syndrome versus obstruction of the third part of the duodenum caused by abdominal aortic aneurysm (AAA), the so-called aortoduodenal syndrome. An upper gastrointestinal contrast study revealed duodenal dilation and blockage of the third part of the duodenum. The AAA continued to enlarge over the subsequent 3 months and the intra-abdominal visceral fat volume decreased over 1 month. The aortomesentric angle and distance remained within normal ranges. Ultimately, the patient was diagnosed with aortoduodenal syndrome. In the present case, a duodenal obstruction was caused by the combination of an enlarged AAA and reduced intra-abdominal visceral fat in a patient receiving maintenance haemodialysis.